Promoting the Online Service Product of PT. Mandiri Sekuritas Using a Promotional Video - Devina Yaphilia (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
This Business Communication Final Project (BCFP) is made for PT. Mandiri Sekuritas, one of the biggest securities company in Indonesia. The background of the study is the fact the most of the Online Service product’s members are passive, or also called as “sleeping clients”. This problem can affect the AR (Assets Ratio) of the company because they are passive traders. Thus, PT. Mandiri Sekuritas needs to make a promotional video. The video will be uploaded in big websites such as YouTube and e-mail. The video is divided into two parts: The first part is dedicated to the people who are new to stocks and the second part is dedicated to the existing members of Mandiri Sekuritas but rarely do anything with their account. In the video, I highlight two things: the importance of joining stock investment and the importance of being active in stocks trading. By making this video, I want to tell all people especially those who are at young age that investment is important for their future and Mandiri can answer their needs very well. Also, those “sleeping clients” can realize that being active will bring them many benefits and that the company cares for them.